Proteksi Panas lebih Pada Generator Berbasiskan Smart Relay - Abdullah, Azmi; Hasyim Rosma, Iswadi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
One of abnormal conditions that may happen when operating synchronous generator is overheating at armature winding. Therefore, this condition is needed to overcome to avoid further damage in the generator by designing and implementing smart relay based overheating protection. Temperature at armature winding is as an input of the smart relay where it was measured by using LM35DZ sensor. Magnetic contactor was used as switch, where it will open when the temperature higher then setting value. The overheat protection design was implemented successfully where it can trip (disconnect generator from the system by opening magnetic contactor) when the armature winding temperature is higher than 60° C.Keyword: Synchronous generator, armature winding, Smart Relay, Temperature Sensor, Zelio Soft 2